Histopathological Review of Granuloma in Diagnosis of Tuberculosis Lymphadenitis (TBL) - Purbaningsih, Wida; Rachmawati, Meike; Triyani, Yani; Rahmi, Fadhilat Sabila (Global Medical & Health Communication (GMHC), 2023)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis and is the second leading cause of death from an infectious disease. Indonesia has the highest TB cases in West Java, East Java, and Central Java. Tuberculosis lymphadenitis (TBL) represents about 30–40% of cases of extrapulmonary tuberculosis. The study aimed to study the clinical and histopathological characteristics of TBL patients. The research design in this study used an exploratory, descriptive method. Data was taken from Al Islam Hospital Bandung as medical records from January 2019 to December 2020. The result showed that TBL primarily affects patients aged 6–11 years (28%), male gender (57%), patients not working (25%), and those residing in the East Bandung area (34%). Histopathological appearance showed granulomas of caseous necrosis, epithelioid cells, and Langhan's cells, indicated by types 1, 2, and 3. The most common type was type 1 (47%), which was more widely distributed in the right neck (46%) with size 1–3 cm. In conclusion, the frequency of TBL is higher in boys aged 6–11 years, residents of the East Bandung area, and patients who did not work. Well-formed granuloma of enlarged lymph nodes in the right neck with size 1–3 cm is most commonly found in TBL.